Politics Of Channels And Geography In Diplomatic Discourse: A Study Of Pakistani Diplomatic Cypher Under Reception Theory - Fatima, Dr. Naeem; Jameel, Sahrish; Mohani, Sobia (Migration Letters, 2024)
The present study aims to understand the themes and politics of the diplomatic discourse inlaid in the Pakistani Diplomatic Cypher written to the Pakistan Foreign Office on March 07, 2022. The study is qualitative based on the analysis of the diplomatic discourse of Pakistani Diplomatic Cypher under the Reception Theory of Cécile Laborde (2002), which includes six different areas of analysis; the themes, politics, areas, channels, temporality, and geography. The study finds that Cypher focuses on different themes and politics based on the different discussion areas. Major discussion areas are the change of chair of Imran Khan, concerns of the US and Western countries about Pakistani foreign policy and remapping it. The study also finds that time and space are much concerned in the discussion of the US representative. The study recommends that the diplomatic Cyphers can be best understood through the knowledge of time, culture, space and history of the nations.